مستقبل منطقة التجارة العربية الحرة في ظل اتفاقيات الشراكة الأورو متوسطية - ربيعة, حملاوي; نجاح, منصري (Sciences humaines; Vol. 33 (2014): SCIENCES HUMAINES, 2014)
تتسم العلاقات الاقتصادية الدولية في وقتنا الحالي بالترابط والتشابك لدرجة كبيرة حيث تسعى معظم دول العالم متقدمة كانت أو نامية إلى تكوين تكتلات وتجمعات اقتصادية سواء كان ذلك في إطار ثنائي أو متعدد، وعلى صعيد الدول العربية وفي سياق سعيها لمواكبة التطورات الحاصلة في العالم عمدت الى السير في اتجاهين مختلفين بغية تحقيق تنميتها الاقتصادية ومسايرتها لمجريات التغير السريع في الاقتصاد العالمي ، ركز الاتجاه الأول على جهودها التكاملية فيما بينها ، حيث يعتبر إنشاء منطقة تجارة حرة عربية مدخل سليم ومنطقي للوصول إلى درجات عليا من التكامل فيما بين الدول العربية بهدف الحفاظ على مصالحها أمام التكتلات الاقتصادية الدولية، أما الاتجاه الثاني فتمثل في توقيع  اتفاقيات التعاون والشراكة مع مختلف التكتلات الاقتصادية، والتي كان أهمها توقيع اتفاقيات الشراكة الأورو متوسطية بين الدول العربية و الاتحاد الأوربي ، وتجدر الاشارة الى ان هذا الأخير بادر بطرح  وتصميم جميع الاتفاقيات المبرمة مع الدول العربية بما يتناسب وأهدافه  دون الأخذ في عين الاعتبار مصالح الدول العربية التكاملية، وذلك لأن الدول العربية تجري مفاوضاتها مع الاتحاد    Abstract :          The International economic relations are characterized, at the present time, by the interrelationship and overlap to a large degree. Most of the world countries, whether developed or developing, look for the formation of blocs and economic groupings, in bilateral or multilateral ways. As to the Arab countries, in the context of their quest to keep up with developments in the world, they proceeded to go on two different trends, in order to achieve economic development and keep up with the course of rapid change in the global economy. The first trend focused on their integration efforts, each other; the establishment of an Arab free trade zone is considered as a good and logical entrance to reach higher degrees of integration between Arab countries, in order to maintain their interests against international economic blocs. The second trend consisted in the signature of cooperation and partnership agreements with various economic blocs; which most important one was the Euro-Mediterranean Partnership, signed between the Arab countries and the European Union. It should be noticed that the latter took the initiative by subtracting and designing all agreements with the Arab states commensurately with their objectives without taking into consideration the integrative interests of the Arab states, because the Arab states conduct negotiations with the European Union individually, therefore, the European Union carry the most bargaining power to ensure its success as a single entity versus dispersed states.